Allele-specific antibodies to Plasmodium vivax merozoite surface protein-1: prevalence and inverse relationship to haemoglobin levels during infection. (December 2016) - Sepúlveda, Nuno; Morais, Cristiane; Mourão, Luiza; Freire, Matheus; Fontes, Cor; Lacerda, Marcus; Drakeley, Chris; Braga, Érika
Abstract Background Antigenic polymorphisms are considered as one of the main strategies employed by malaria parasites to escape from the host immune responses after infections. Merozoite surface protein-1 (MSP-1) ofPlasmodium vivax, a promising vaccine candidate, is a highly polymorphic protein whose immune recognition is not well understood. Methods and results The IgG responses to conserved (MSP-119 ) and polymorphic (block 2 and block 10) epitopes of PvMSP-1 were evaluated in 141P. vivax infected patients. Ten recombinant proteins corresponding to block 2 (variants BR07, BP29, BP39, BP30, BEL) and block 10 (BR07, BP29, BP39, BP01, BP13) often observed in BrazilianP. vivax isolates were assessed by ELISA in order to determine levels of specific antibodies and their respective seroprevalence. The magnitude and the frequency of variant-specific responses were very low, except for BR07 variant (>40%), which was the predominant haplotype as revealed by block 10 PvMSP-1 gene sequencing. By contrast, 89% of patients had IgG against the C-terminal conserved domain (PvMSP-119 ), confirming the high antigenicity of this protein. Using multiple linear and logistic regression models, there was evidence for a negative association between levels of haemoglobin and several IgG antibodies against block 2 variant antigens, with the strongest association being observed for BP39 allelic version. This variant was also found to increase the odds of anaemia in these patients. Conclusions These findings may have implications for vaccine development and represent an important step towards a better understanding of the polymorphic PvMSP-1 domain as potential targets of vaccine development. These data highlight the importance of extending the study of these polymorphic epitopes of PvMSP-1 to different epidemiological settings.